CLIMATE VILLAGE PROGRAM PLANNING (PROKLIM) IN UMBAN SARI VILLAGE, RUMBAI DISTRICT, PEKANBARU CITY (CASE STUDY RW 12 & RW 13) - Sri Roserdevi Nasution; Harsini; Bima Ramadhan Saputra; Fajarwaty Kusumawardhani (JURNAL SOSIO-KOMUNIKA, 2023)
This study discusses the planning of the climate village program in RW 12 and RW 13, Umbansari Village, Rumbai District. Proklim is a program which has a national scope managed by the Ministry of Environment and Forestry in order to increase community participation in participating and carrying out adaptation activities to the impacts of climate change and GHG emission reduction and to provide recognition for adaptation and mitigation efforts. climate change is taking place. The phenomena found in this study are the lack of supporting data for submitting the climate village program, such as institutional data and data on adaptation mitigation action activities and a lack of understanding from the community regarding the climate village program. This study aims to determine and analyze the planning of the climate village program in Umban Sari Village, Rumbai District, Pekanbaru City and to determine the inhibiting factors in planning the climate village program in Umban Sari Village, Rumbai District, Pekanbaru City. The theory used in this study is to use Hani Handoko's theory. Setting goals and a series of activities, formulating the current situation, identifying all facilities and obstacles, developing a plan or series of activities to achieve goals. This study used a qualitative method, namely by taking a phenomenological approach and collecting data using interview techniques, direct observation and documentation. The results of this study are that targets have not been achieved according to proklim standardization due to obstacles in proklim planning such as obstacles that exist in this research location caused by the community not understanding what the climate village program is and the lack of institutional data and action data on adaptation mitigation activities which causes planning in Umban sari Village has not reached the target.